2018
DOI: 10.1111/hex.12678
|View full text |Cite
|
Sign up to set email alerts
|

Improving health literacy in a Japanese community population—A pilot study to develop an educational programme

Abstract: ObjectiveAlthough a growing number of interventional studies on health literacy have been conducted recently, the majority were designed in clinical settings, focusing mainly on functional health literacy. This study evaluated a programme designed to improve health literacy in a community population, with a scope of going beyond functional health literacy.MethodsIn collaboration with an Approved Specified Nonprofit organization (NPO), we evaluated a five‐session programme designed to provide basic knowledge on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 35 publications
2
29
1
Order By: Relevance
“…Individuals with a high economic status are more likely to have the advantage that they can easily use equipment to collect health information and that they can easily access the healthcare system. It is expected that the health literacy of the general population would improve through the use of health information and interaction with healthcare providers 44 …”
Section: Discussionmentioning
confidence: 99%
“…Individuals with a high economic status are more likely to have the advantage that they can easily use equipment to collect health information and that they can easily access the healthcare system. It is expected that the health literacy of the general population would improve through the use of health information and interaction with healthcare providers 44 …”
Section: Discussionmentioning
confidence: 99%
“…Improving people’s health literacy is one of the most basic, effective, and economic measures to improve the health of the whole population [ 9 , 22 ]. Improved HL levels contribute to increased health outcomes, well-being, and reduced health inequalities [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that low levels of HL are of prognostic importance for various negative health effects [ 2 , 5 , 6 , 7 ]. It is also related to higher health care costs [ 8 , 9 ]. Research shows that a lower degree of health knowledge is associated with poorer mental and physical health [ 8 ] and adverse health behaviours such as: lower ability to take care of oneself [ 10 ], higher percentage of avoidable hospitalisations [ 6 , 11 ], and less frequent use of preventive health services [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings point to the need to develop healthcare literacy programs targeting ED use. A number of community-based strategies for increasing health literacy have proven effective [ 29 , 30 ]. A possible approach for a comprehensive intervention that are hoped to increase patient engagement is the use of the social-ecological model [ 31 ].…”
Section: Discussionmentioning
confidence: 99%